HISTORICAL TRANSFORMATIONS OF HERMENEUTICS M. HEIDEGGER - Vira Dubinina ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Hermeneutics of presence, developed by M. Heidegger, and possible ways of its further transformation are considered. This tendency was embodied and developed in the project of philosophical hermeneutics H.-G. Gadamer, who focuses not on the analytics of presence, but on the language as a horizon of meaning and understanding. A comparative analysis of these theories shows that the understanding of hermeneutics as an ontological interpretation of presence is completed not only in the framework of ontological discourse, but also in the representation of language as an independent agent, which is also the most developed topos of existence. The analytics of presence is the main content of Heidegger's main work, and at the same time it should become the basis of the fundamental ontology, which grows directly from such hermeneutics and, in a sense, is its substantive mode. Such a theory is an understanding that is carried out not as an act of thinking, but as a way of staying, a special Dasein modus, which is given not so much epistemologically as existentially. Although Gadamer lacks the required hermeneutic analytics of the language, he never departs from his postulate of the linguistic nature of understanding. For him, the soil on which human existence is built as understanding is initially language, while Heidegger comes to language through speech, which is seen as the existential-ontological foundation of language. Language, according to Gadamer, is an a priori condition for any act of understanding, the space for its implementation and, at the same time, the result, expressed in the total "stipulation" of the world by the word.